Pengaruh Career Development Terhadap Job Satisfaction pada Mahasiswa Karyawan - Rismawati, Rismawati; Hidayat, Novi; Ikromi, Ziyadi Ali (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
Job satisfaction is an expression that indicates satisfaction with the results of an evaluation of work and its characteristics. Career development is one of the factors of job satisfaction. Career development is a continuous process in which individuals acquire the skills, knowledge, and experience necessary to achieve their career goals. The purpose of this study is to determine the effect of career development on job satisfaction among student employees in Greater Jakarta. The sample in this study consisted of 109 student employees selected using non-probability sampling, specifically purposive sampling. Confirmatory Factor Analysis (CFA) was used to test the construct validity of each variable. Statistical testing using multiple regression analysis was employed to examine the influence of the independent variable (career development) on the dependent variable (job satisfaction). The results of the study indicate that there is a significant influence of career development on job satisfaction with an R Square proportion of 30.4%. For further research, it is recommended to investigate whether human resource management is a factor that strengthens or weakens the influence of career development on job satisfaction. Additionally, companies are advised to enhance their perception of the value of career development to further increase job satisfaction among employees.